Extrusion Technology: A Tool for Value Addition to Food By-Products and Wastes - T. A. Dendegh; B. M. Yelmi; M. J. B. Abdullahi (Archives of Current Research International, 2021)
The food processing industry generates an immense amount of waste and by-products, which leads to major concerns about the environment. However, most of these wastes, such as plant-derived by-products, are still nutritionally adequate for use in food manufacturing processes. Extrusion technology has brought rapid transformation, new research ideas, opportunities and innovations in the food processing industries. Owing to its versatile nature and many advantages it has over other types of processing methods, a wide range of food raw materials could be processed conveniently which are microbiologically safe and also retain nutrients under carefully selected conditions. It is effluents free during processing; therefore, has no negative impact on the environment and fewer worries about waste or effluent disposal. It has been shown by many authors how extrusion technology is applied to process safe and convenient food products from industrial by-products and waste generated during processing. By-products such as bran, grits, hulls, grape pomace, carrot pomace, apple pomace, were combined or formulated with other food such as corn amongst others to make products like biscuits, pasta amongst using extrusion technology. This is carried out under a controlled process and system parameters to ensure the best product quality. Additionally, anti-nutritional factors present in some of these by-products can be minimized by the extrusion process for use as a food additive or in the formulation of balanced foods. This review features the past research on the value addition process by extrusion to food processing by-products and wastes from fruits and vegetables, cereals and pulses and oilseed (cakes) processing amongst others.